Eksplorasi dan Karakterisasi Khamir dan Bakteri sebagai Agens Antagonis terhadap Penyebab Penyakit Blas pada Padi - Jauharoh Maknunah; Meity Suradji Sinaga (Jurnal Fitopatologi Indonesia, 2018)
Exploration of Yeasts and Bacteria as Antagonist Agent of Rice Blast Pathogen Blast disease (Pyricularia oryzae) is a major disease of rice that causes 61% yield losses. An alternative way to control the disease is applying antagonistic agents, both yeasts and bacteria. This study was aimed to obtain yeast and bacterial isolates that can be used as antagonistic agents to effectively control blast disease. Yeasts and bacteria were isolated from the leaves of Digitaria sp., Panicum sp., and Pennisetum sp.. The isolates of yeasts and bacteria were screened following hypersensitive test on tobacco leaves, direct planting method test on ‘Ciherang’ rice seed, and hemolysis test on blood agar medium. The isolates were also further assayed for their antagonism through dual culture test, volatile compound test, hyperparasitism test, and chitinolytic activity test. Three isolates of yeast, i.e. Cryptococcus sp., Rhodotorula sp., and Candida sp., and two bacterial isolates, i.e. Bacillus sp. and isolate PPY were identified as potential antagonists of P. oryzae.